Quality of dorzolamide hydrochloride and timolol maleate containing eye drops distributed online - Sára Merczel; Róbert György Vida; Tamás Tasi; András Fittler; Lajos Botz (Elsevier, 2023)
Patient safety risks associated with the online purchase of medications, especially in case of ophthalmic preparations, are significant. Our study aimed to carry out quality assessment of dorzolamide hydrochloride (DZA) and timolol maleate (TIM) eye drops preserved with benzalkonium chloride (BAC) via online test purchases.Three samples were purchased online, while control preparations were acquired through authorized national drug supply chain. Our method was based on the International Pharmaceutical Federation (FIP) Inspection Checklist and integrated the evaluation of packaging and labelling. Sterility was established according to the European Pharmacopoeia (Ph. Eur.), while qualitative and quantitative quality was assessed with high-performance liquid chromatographic (HPLC) analysis.Several signs of falsification were recognized upon visual inspection of the online samples. All the products were clear, colourless, slightly viscous solutions. They were free from visible contaminants. The samples were sterile as no evidence of microbial growth was found. A quick and inexpensive HPLC analysis, optimized by the authors showed that active ingredients and the preservative deviated significantly (p < 0,05) with more than 10% from the values stated on the labels for at least one component (DZA: 99.3-113.1%, TIM: 112.8-139.2%, BAC: 82.4-97.7%).Development of comprehensive and reliable quality assessment methods are vital to increase public safety of pharmaceutical products sold online. A complex approach, integrating visual inspection, labelling assessment, microbiological analysis coupled with qualitative and quantitative methods provide a most reliable method. Due to its limited feasibility and cost-effectiveness, raising public awareness and limiting illegal online sellers should be the primary approaches to protect patients from substandard and falsified medicinal products sold via the internet. Particularly important for health professionals to understand this market and its public health concern, and to raise patient awareness of the risks associated with uncontrolled online purchase of medication.